钌配位聚吡咯纳米球团簇材料及其制备方法和应用 (2018)
本发明公开了种钌配位聚吡咯纳米球团簇材料及其制备方法和应用，所述的钌配位聚吡咯纳米球团簇材料由钌配位聚吡咯纳米球构成，纳米球紧密堆积形成纳米球团簇，纳米球团簇相互聚集形成纳米球团簇间微孔。钌配位聚吡咯纳米球团簇材料采用单体配位-电聚合法制备。首先采用直接配位反应合成法，利用钌离子的空轨道和吡咯单体分子链上氮原子的未成对电子相互作用，通过直接配位反应制得钌配位吡咯单体。然后采用循环伏安电聚合反应合成法，钌配位吡咯单体在π-π堆积力作用下，通过电聚合反应制得钌配位聚吡咯。相对于现有技术，所述材料具有较大的比表面积、较好的导电性和结构稳定性，在电化学应用中表现出更优异的电容性能和电化学稳定性。 The invention discloses a ruthenium coordinated polypyrrole nanosphere cluster material and a preparation method and application thereof. The ruthenium coordinated polypyrrole nanosphere cluster material is formed by ruthenium coordinated polypyrrole nanospheres, and the nanospheres are closely accumulated to form nanosphere clusters which are gathered to form nanosphere inter-cluster micropores. The ruthenium coordinated polypyrrole nanosphere cluster material is prepared according to a monomer coordination-electropolymerization method. Firstly, according to a direct coordination reaction method, ruthenium coordinated polypyrrole monomers are prepared under interaction of unpaired electrons of nitrogen atoms on pyrr